Legibilidades, un trabajo sobre el sentido: silencio y discursos en la formación de una dicción sobre la Dictadura (ensayo y novela) (El Hilo de la Fabula, 2010)
This work tries to present a reflection on silence in Literature postdictatorship in Argentina. We considered that the novel and the test are creating a new diction that reviews the dictatorship, its representations, their senses and imaginary groups. Silence, topic simultaneously that impossibility to speak, now is put in evidence like problem and cuestionamiento to doxa underlying. The examples taken in consideration allow verifying this hypothesis.